Erp57 facilitates ZIKV-induced DNA damage via NS2B/NS3 complex formation - Yiran Wang; Dan Song; Yichen Li; Leiying Qin; Qianya Wan; Huan Hu; Mandi Wu; Yaxiu Feng; Luis Schang; Robert Weiss; Ming-Liang He (Emerging Microbes and Infections)
It is believed that DNA double-strand breaks induced by Zika virus (ZIKV) infection in pregnant women is a main reason of brain damage (e.g. microcephaly, severe brain malformation, and neuropathy) in newborn babies [1,2], but its underlying mechanism is poorly understood. In this study, we report that the depletion of ERp57, a member of the protein disulphide isomerase (PDI) family, leads to the limited production of ZIKV in nerve cells. ERp57 knockout not only suppresses viral induced reactive oxygen species (ROS) mediated host DNA damage, but also decreases apoptosis. Strikingly, DNA damage depends on ERp57-bridged complex formation of viral protein NS2B/NS3. LOC14, an ERp57 inhibitor, restricts ZIKV infection and virus-induced DNA damage. Our work reveals an important role of ERp57 in both ZIKV propagation and virus-induced DNA damage, suggesting a potential target against ZIKV infection.